2012
DOI: 10.1056/nejmoa1208872
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic Therapy vs. OnabotulinumtoxinA for Urgency Urinary Incontinence

Abstract: BACKGROUND Anticholinergic medications and onabotulinumtoxinA are used to treat urgency urinary incontinence, but data directly comparing the two types of therapy are needed. METHODS We performed a double-blind, double-placebo–controlled, randomized trial involving women with idiopathic urgency urinary incontinence who had five or more episodes of urgency urinary incontinence per 3-day period, as recorded in a diary. For a 6-month period, participants were randomly assigned to daily oral anticholinergic medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
129
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 196 publications
(144 citation statements)
references
References 19 publications
(22 reference statements)
10
129
4
1
Order By: Relevance
“…This can be explained by the fact that neurogenic bladders are often more refractory to medical therapies, as pointed out by Horstmann and colleagues. 22 A 94% success rate in the non-neurogenic group is therefore reassuring since other treatments, such as intravesical oxybutynin, sacral neuromodulation or botulinum toxin (with their inherent 5% to 11% risk of clean intermittent catheterization), 23,24 would be deferred. For non-responders or children responding only partially to therapy, initial urodynamics were less favourable (stronger uninhibited detrusor contractions and smaller bladder capacity).…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the fact that neurogenic bladders are often more refractory to medical therapies, as pointed out by Horstmann and colleagues. 22 A 94% success rate in the non-neurogenic group is therefore reassuring since other treatments, such as intravesical oxybutynin, sacral neuromodulation or botulinum toxin (with their inherent 5% to 11% risk of clean intermittent catheterization), 23,24 would be deferred. For non-responders or children responding only partially to therapy, initial urodynamics were less favourable (stronger uninhibited detrusor contractions and smaller bladder capacity).…”
Section: Discussionmentioning
confidence: 99%
“…The full methods of the ABC trial and its primary results have been published elsewhere [7,8]. Clinical sites are supported by a data coordinating center, an NIH Project Scientist, and an external Steering Committee Chair.…”
Section: Methodsmentioning
confidence: 99%
“…This has been due to the positive results obtained in multiple randomized trials with the use of Onabot/A in idiopathic OAB patients, which has definitely confirmed the high efficacy and tolerability of this kind of minimally invasive treatment (7)(8)(9). Nevertheless, to date, we still need to establish what is the best Onabot/A treatment's protocol for patients affected by idiopathic OAB, and what is the more appropriate care of patient before, during and after treatment.…”
Section: Original Articlementioning
confidence: 99%